Counteracting market concentration in renewable energy auctions: Lessons learned from South Africa. (January 2021) - Kruger, Wikus; Nygaard, Ivan; Kitzing, Lena
Abstract: Competitive bidding programmes, or auctions, are becoming the dominant method for procuring utility-scale renewable energy generation capacity and have coincided with significant cost reductions of renewable energy (RE) technologies. The use of price in auctions as the main awarding criterion has been criticized for apparently leading to market concentration and dominance in project ownership. We investigate: to what extent South Africa's renewable energy auction programme has contributed to market concentration and dominance; if market concentration and dominance have a negative impact on electricity cost in the auction; and to what extent measures taken to counteract market concentration and dominance have led to improved competition and diversity of project ownership. The study analyses bidding data from awarded solar photovoltaic (PV) and wind projects, complemented by interviews with key stakeholders in the industry and in government. While there has been some degree of market concentration, it was not observed to have an adverse impact on project pricing or market development. Introducing preferential conditions for small, local players has been more effective at counteracting market concentration than an overall lowering of entry barriers. Finally, policy certainty and predictability seem more important to counteract market concentration and dominance than any auction design measures. Highlights: South Africa's renewable energy auctions have led to some market concentration. Market concentration appears not to have resulted in market domination. Market concentration coincided with increasing competition and lower project prices. Preferential procurement conditions can limit market concentration. Policy certainty is also needed to counteract market concentration and dominance.